Kajian Nilai Tukar Petani Indonesia dalam Perspektif Sustainable Development Goals - Nurfajari, Afini (JURNAL KEPARIWISATAAN, 2024)
The agriculture sector is critical to the achievement of the first and second Sustainable Development Goals (SDGs). Studying the Farmer Exchange Rate provides insight into the impact of this exchange rate and its influencing elements from the standpoint of the SDGs. One of the issues is the necessity for farmers to gain greater expertise. The purpose of this research is to examine the relationship between the Indonesian Farmer Exchange Rate and the SDGs. A literature review was used in this study, using secondary data gathered from papers and journals containing talks on Farmer Exchange Rates and SDGs that were curated and identified as many as 40 selected research titles. Data analysis was carried out in stages that included data gathering, data reduction, presentation, and conclusion drafting. Data was gathered from the Published or Perish application utilizing Google Scholar literature sources. According to the study's findings, the Farmer Exchange Rate corresponds with poverty, a key target of the SDGs. Because the Farmer Exchange Rate is a measure of farmer welfare, which is tied to poverty, the factors that influence it also affect the SDGs. Lower poverty rates are connected with higher farmer welfare.